Cannabinoid Receptor Agonist WIN55, 212-2 Adjusts Lipid Metabolism in a Rat Model of Cardiac Arrest - Xiao, Yan (Ther Hypothermia Temp Manag, 2020)
The objective of this study was to investigate the effects of pharmacologically induced hypothermia with WIN55, 212-2 (WIN)on postresuscitation myocardial function, microcirculation, and metabolism-specific lipids in a rat cardiac arrest (CA) model. Ventricular fibrillation was electrically induced and untreated for 6 minutes in 24 Sprague-Dawley rats weighing 450–550 g. Cardiopulmonary resuscitation including chest compression and mechanical ventilation was then initiated and continued for 8 minutes, followed by defibrillation. At 5 minutes after restoration of spontaneous circulation (ROSC), animals were randomized into four groups: (1) normothermia with vehicle (NT); (2) physical hypothermia with vehicle (PH); (3) WIN55, 212-2 with normothermia (WN); and (4) WIN55, 212-2 with hypothermia (WH). For groups of WN and WH, WIN was administered by continuous intravenous infusion with a syringe pump for 4 hours. PH started at 5 minutes after resuscitation. NT maintained core temperature at 37°C ± 0.2°C with the aid of a heating blanket. Hypothermia groups maintained temperature at 33°C ± 0.5°C for 4 hours after ROSC. There was a significant improvement in myocardial function as measured by ejection fraction, cardiac output, and myocardial performance index in animals treated with WH and PH beginning at 1 hour after start of infusion. In the WH and PH groups, buccal microcirculation was significantly improved compared with NT and WN. Plasma at pre-CA and ROSC 4 hours was harvested for lipid metabolism. The WH group appeared to be closer to baseline than the other groups in lipid metabolism. lysophosphatidylcholine (LPC) 18:2, free fatty acid (FFA) 22:6, and ceramide (CER) (24:0) changed significantly among the lipidomic data compared with NT (p < 0.05). Postresuscitation hypothermia improved myocardial function and microcirculation. WH-mediated lipid metabolism had the best metabolic outcome to bring back the animals to normal metabolism, which may be protective to improve outcomes of CA. LPC 18:2, FFA 22:6, and CER (24:0) may be important predictors of outcomes of CA.